The effect of exercise on academic fatigue and sleep quality among university students - Li, Wenjing; Chen, Jianing; Li, Mingping; Smith, Andrew P.; Fan, Jialin (Frontiers in Psychology, 2022)
Background: Routine academic events may cause fatigue and impair sleep quality. This research aimed to examine the prevalence and risk factors for academic fatigue among college students and its adverse effects on well-being and sleep. A brief exercise intervention was also evaluated Methods: 864 college students (33.5% female) filled out self-reported questionnaires with few open-ended questions. Fatigue and sleep quality were assessed using the translated version of the Smith Well-being Questionnaire and the Chinese version of the Pittsburgh Sleep Quality Index (PSQI). Spearman correlations, logistic regression analysis, and t-tests were used to test the hypotheses. In a second study, 29 female participants took part in an exercise intervention aimed at reducing fatigue and improving sleep. Results: Among the effective respondents, nearly 40% reported higher academic-related fatigue, and a few reported high-quality sleep. Negative coping styles, workload, stress, and disturbed surroundings had a significant positive predictive effect on academic fatigue. In addition, adverse consequences of fatigue were found for physical health and academic-life balance, and a significant, positive relationship was observed between the degree of fatigue and PSQI score (p<0.01). The exercise study showed some beneficial effects of the intervention for both sleep and fatigue outcomes. Conclusions: Fatigue is common and widely reported among Chinese college students, and it may have a major negative impact on their health. Increased awareness of daily academic fatigue and its impact on college students is important for individuals, schools, and society. Exercise may be a simple way to improve sleep and reduce fatigue.